Optical solitons with anti-cubic nonlinearity using three integration schemes - Jawad, Anwar Ja'afar Mohamad; Mirzazadeh, Mohammad; Zhou, Qin; Biswas, Anjan (Superlattices and microstructures, 2017)
This paper employed three integration schemes to obtain soliton solutions in optical fibers with anti-cubic nonlinearity. These are traveling waves, tanh-coth scheme and finally the modified simple equation method. These yielded bright solitons, singular solitons, dark-singular combo solitons and other waves. The existence criteria for these solitons are presented. The paper concludes with a discussion on conservation laws. •Solitons in optical fibers with anti-cubic nonlinearity are studied.•Bright, singular and dark-singular combo solitons are constructed.•Traveling waves, tanh-coth scheme and modified simple equation method are used.